Minimizing cost and time through single objective function in multi-choice interval valued transportation problem - Roy, Sankar Kumar; Maity, Gurupada (Journal of intelligent & fuzzy systems, 2017)
This paper explores the study of Transportation Problem (TP) under the light of multi-choice environment with interval analysis. The parameters of TP follow multi-choice interval-valued type so this form of TP is called Multi-Choice Interval Transportation Problem (MCITP). Introduction of time is an important notion in TP of this paper. Transportation time and cost, both are minimized through single objective function of TP, which is the main aim of this paper. A procedure is shown for converting from MCITP to deterministic TP and then solve it. A case study is included to illustrate the usefulness of the paper. Finally, concluding remarks and an outlook for future study are presented to this paper.